2018
DOI: 10.1002/hed.25338
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal renal cell‐like adenocarcinoma: Easily misdiagnosed sinonasal tumor

Abstract: This is the first study to review the clinical features of sinonasal renal cell-like adenocarcinoma. We recommend surgical resection as the mainstay of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…On MR imaging, the tumors are heterogeneous to the cortex on T2WI and enhance avidly, similar to renal cell carcinoma. [54][55][56] A key diagnostic criterion is the lack of a concomitant suspicious renal mass (Fig 9).…”
Section: Renal Cell-like Adenocarcinomamentioning
confidence: 99%
“…On MR imaging, the tumors are heterogeneous to the cortex on T2WI and enhance avidly, similar to renal cell carcinoma. [54][55][56] A key diagnostic criterion is the lack of a concomitant suspicious renal mass (Fig 9).…”
Section: Renal Cell-like Adenocarcinomamentioning
confidence: 99%
“…Eight, including our case, underwent additional RT and none received systemic therapy. Wu et al reported the only known case of local recurrence [ 9 ]. Their patient was treated with surgical excision alone and was found to have a recurrence 35 months after primary resection.…”
Section: Discussionmentioning
confidence: 99%
“…SNRCLA is an extremely rare neoplasm, which only 19 cases have been reported in the English literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. SNRCLA was rst decribed as low grade adenocarcinoma of the nasal cavity and parenasal sinuses by heffner et al [2].…”
Section: Discussionmentioning
confidence: 99%